Hybridity and Authenticity of Ichwan Noor’s Sculpture: A Case Study of Bedhaya Kinjeng Wesi Sculpture in Yogyakarta International Airport - Witjaksono, Bambang (Institut Seni Indonesia Yogyakarta, 2025)
The Bedhaya Kinjeng Wesi (literally mean Iron Dragonfly Bedhaya) sculpture represents a significant intersection of traditional Javanese culture and contemporary art at Yogyakarta International Airport (YIA). This study examines how hybridity and authenticity manifest in this commissioned artwork created by sculptor Ichwan Noor between September 2019 and January 2020. Using qualitative methods including participant observation, visual documentation, and interviews, this research analyzes the complex negotiation process that occurred between institutional stakeholders, cultural authorities, and artistic vision. The findings reveal that the sculpture’s creation involved a unique creative sequence: first, a traditional dance form (Bedhaya Kinjeng Wesi Dance) was developed as reference material, then reinterpreted through contemporary sculptural techniques. The resulting artwork demonstrates hybridity through its combination of traditional dance postures, symbolic elements from local oral tradition, and modern materials and aesthetics. This case study contributes to our understanding of how authenticity is negotiated in public art that serves both cultural representation and tourism functions, particularly in postcolonial contexts where local identity intersects with global modernity. Rather than seeing hybridity and authenticity as opposing forces, this research suggests they operate as complementary processes in contemporary cultural production. Hibriditas dan Keaslian Patung Ichwan Noor: Studi Kasus Patung Bedhaya Kinjeng Wesi di Bandara Internasional Yogyakarta. Patung Bedhaya Kinjeng Wesi merupakan persimpangan penting antara budaya Jawa tradisional dan seni kontemporer di Bandara Internasional Yogyakarta (YIA). Studi ini menggunakan metode kualitatif meneliti bagaimana hibriditas dan keaslian terwujud dalam karya seni yang dipesan oleh pematung Ichwan Noor antara September 2019 hingga Januari 2020 termasuk observasi partisipan, dokumentasi visual, dan wawancara. Penelitian ini menganalisis proses negosiasi kompleks yang terjadi antara pemangku kepentingan institusional, otoritas budaya, dan visi artistik. Temuan penelitian mengungkapkan bahwa penciptaan patung tersebut melibatkan urutan kreatif yang unik: pertama, bentuk tari tradisional dikembangkan sebagai bahan referensi, kemudian ditafsirkan ulang melalui teknik pahatan kontemporer. Karya seni yang dihasilkan menunjukkan hibriditas melalui kombinasi postur tari tradisional, elemen simbolis dari tradisi lisan lokal, dan bahan serta estetika modern. Studi kasus ini memberikan kontribusi pada pemahaman tentang bagaimana keaslian dinegosiasikan dalam seni publik yang berfungsi sebagai representasi budaya dan fungsi pariwisata, khususnya dalam konteks pascakolonial, yaitu identitas lokal bersinggungan dengan modernitas global. Alih-alih melihat hibriditas dan keaslian sebagai kekuatan yang berlawanan, penelitian ini menunjukkan bahwa keduanya beroperasi sebagai proses yang saling melengkapi dalam produksi budaya kontemporer.